2022
DOI: 10.3390/cancers14092319
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of IGF2 mRNA-Binding Protein 3 (IGF2BP3) Intratumoral Expression in Melanoma Patients at the Time of Diagnosis: Comparative Analysis of RT-qPCR Versus Immunohistochemistry

Abstract: Screening for prognostic biomarkers is crucial for clinical melanoma management. Insulin-like growth factor-II mRNA-binding protein 3 (IGF2BP3) has emerged as a potential melanoma diagnostic and prognostic biomarker. It is commonly tested by immunohistochemistry (IHC). Our study retrospectively examines IGF2BP3 mRNA and protein expression in primary melanomas, their correlation with clinicopathologic factors, clinical outcome, and selected miRNAs expression, and their efficiency in predicting melanoma progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…High IGF2BP3 expression is possibly associated with poor prognosis in nasopharyngeal carcinoma [22], colon cancer [23], lung adenocarcinoma [24], acute myeloid leukemia [25], endometrial carcinoma [26], and melanoma [27]. The bioinformatics database analysis showed that in COAD, the low and high IGF2BP3 expression groups showed large differences in the TME [23].…”
Section: Discussionmentioning
confidence: 99%
“…High IGF2BP3 expression is possibly associated with poor prognosis in nasopharyngeal carcinoma [22], colon cancer [23], lung adenocarcinoma [24], acute myeloid leukemia [25], endometrial carcinoma [26], and melanoma [27]. The bioinformatics database analysis showed that in COAD, the low and high IGF2BP3 expression groups showed large differences in the TME [23].…”
Section: Discussionmentioning
confidence: 99%